Youth, policing and democratic accountability: a study in applied critical theory - Loader, Ian (The University of Edinburgh, 1994)
This thesis is concerned with the relationship between young people and policing. It draws upon the resources of contemporary social and political theory, and interviews with young people (aged 15-23) and police officers in Edinburgh, in order to explicate the possibility of democratic communication between youth and the police, and analyse the consequences of its absence.

Theoretically, it delineates an applied reformulation of Jurgen Habermas’ theory of communicative action that can expedite a grounded investigation of the relationship between youth, crime and policing. In this regard, Habermas’ work (i) shapes the elucidation of a prefigurative methodological approach to the relevant substantive issues, and (ii) serves as a standpoint from which to review the existing sociological literature on both youth culture and policing. In this latter context, it specifically informs the generation - through a reconstruction of subcultural theory - of an original theoretical framework within which to make sense of the accounts constructed in interviews with young people and police officers.

Using this framework, the substantive research explores the ways in which young people and police officers communicate their respective experiences and dispositions. In particular, it moves beyond the conventional criminological focus on juvenile delinquency, and expounds the various ways in which young people experience and apprehend crime in public places. Conversely, it assesses how police officers understand and relate to youth social practices (whether in terms of pedagogic promotion or control). In both cases, the analysis is further solicitous to the impact that different post-school economic trajectories have upon youth practices and the policing of them. Finally, the substantive enquiry examines both the possibilities of communication between young people and police officers, and some of the obstacles that stand in its way.

The thesis concludes by drawing together the conceptual and substantive dimensions of the enquiry in order to think anew about the vexed question of police accountability. It endeavours, in particular, to redeem an interest in the question of democratic accountability by (i) articulating a number of questions that, it is argued, any proposals for police accountability must address, and (ii) outlining a series of institutional proposals that, if enacted, might resolve some of the existent tensions in police-youth relations in ways that involve the discursive negotiation of both the police and the policed.